Migration of photoinitiators from cardboard into dry food: evaluation of Tenax® as a food simulant. Issue 5 (3rd May 2016) - Van Den Houwe, Kathy; Evrard, Caroline; Van Loco, Joris; Lynen, Frederic; Van Hoeck, Els
ABSTRACT: Photoinitiators are widely used to cure ink on packaging materials used in food applications such as cardboards for the packaging of dry foods. Conventional migration testing for long-term storage at ambient temperature with Tenax ® was applied to paperboard for the following photoinitiators: benzophenone (BP), 4, 4ʹ- bis (diethylamino)benzophenone (DEAB), 2-chloro-9H-thioxanthen-9-one (CTX), 1-chloro-4-propoxy-9H-thioxanthen-9-one (CPTX), 4-(dimethylamino)benzophenone (DMBP), 2-ethylanthraquinone (EA), 2-ethylhexyl-4-dimethylaminobenzoate (EDB), ethyl-4-dimethylaminobenzoate (EDMAB), 4-hydroxybenzophenone (4-HBP), 2-hydroxy-4-methoxybenzophenone (HMBP), 2-hydroxy-4ʹ-(2-hydroxyethoxy)-2-methylpropiophenone (HMMP), 2-isopropyl-9H-thioxanthen-9-one (ITX), 4-methylbenzophenone (MBP) and Michler's ketone (MK). Test conditions (10 days at 60°C) were according to Regulation (EU) No. 10/2011 and showed different migration patterns for the different photoinitiators. The results were compared with the migration in cereals after a storage of 6 months at room temperature. The simulation with Tenax at 60°C overestimated actual migration in cereals up to a maximum of 92%. In addition, the effect of a lower contact temperature and the impact of the Tenax pore size were investigated. Analogous simulation performed with rice instead of Tenax resulted in insufficiently low migration rates, showing Tenax is a much stronger adsorbent than rice and cereals.